'Difficult temperament' linked to preschooler mental health problems: BELLA study. Issue 5 (May 2017) - Knopf, Alison
Abstract : The single most important risk factor for preschool mental health problems is a difficult temperament, researchers have found. If parents perceive themselves as competent, their preschool‐aged children are less likely than others to have mental health problems. After controlling for other factors, parental mental health problems and low socioeconomic status did not increase the child's likelihood of mental health problems.